Posterior semicircular canal dehiscence: a diagnostic and surgical conundrum. Issue 7 (2nd July 2019) - Philip, Ajay; Mammen, Manju Deena; Lepcha, Anjali; Alex, Anu
Abstract : Third window defects have increasingly been identified as a cause of vertigo. These defects are bony dehiscences that occur in the bony labyrinth, resulting in abnormal pressure gradient in the inner ear fluids leading to sound (Tullio's phenomenon) or pressure (Hennebert's sign) induced vertigo. The superior semicircular canal dehiscence syndrome is a well-described entity in this regard, however defects of the posterior semicircular canal are rare and may have overlapping symptomatology. We describe the history, clinical profile and management of a patient who had importunate symptoms despite being on conservative management for a year and had resolution of vestibular symptoms following surgical management.